A comparative study of gasoline skeletal mechanisms under partial fuel stratification conditions using large eddy simulations. (October 2022) - Guleria, Gaurav; Lopez-Pintor, Dario; Dec, John E; Assanis, Dimitris
Partial fuel stratification (PFS) is a low temperature combustion strategy that can alleviate high heat release rates of traditional low temperature combustion strategies by introducing compositional stratification in the combustion chamber using a split fuel injection strategy. In this study, a three-dimensional computational fluid dynamics (CFD) model with large eddy simulations and reduced detailed chemistry was used to model partial fuel stratification at three different stratified conditions. The double direct injection strategy injects 80% of the total fuel mass at −300 CAD aTDC and the remaining 20% of the fuel mass is injected at three different timings of −160, −50, −35 CAD to create low, medium, and high levels of compositional stratification, respectively. The PFS simulations were validated using experiments performed at Sandia National Laboratories on a single-cylinder research engine that operates on RD5-87, a research-grade E10 gasoline. The objective of this study is to compare the performance of three different reduced chemical kinetic mechanisms, namely SKM1, SKM2, and SKM3, at the three compositional stratification levels and identify the most suitable mechanism to reproduce the experimental data. Zero-dimensional chemical kinetic simulations were also performed to further understand differences in performance of the three reduced chemical kinetic mechanisms to explain variations in CFD derived heat release profiles. The modeling results indicate that SKM3 is the most suitable mechanism for partial fuel stratification modeling of research-grade gasoline. The results also show that the autoignition event progresses from the richer to the leaner compositional regions in the combustion chamber. Notably, the leaner regions that have less mass per unit volume, can contribute disproportionately more toward heat release as there are more cells at leaner equivalence ratio ranges. Overall, this study illuminates the underlying compositional stratification phenomena that control the heat release process in PFS combustion.